Common Threads : A Cultural History of Clothing in American Catholicism - Dwyer-McNulty, Sally (Book collections on Project MUSE., 2014)
A well-illustrated cultural history of the apparel worn by American Catholics, Sally Dwyer-McNulty's Common threads reveals the transnational origins and homegrown significance of clothing in developing identity, unity, and a sense of respectability for a major religious group that had long struggled for its footing in a Protestant-dominated society often openly hostile to Catholics. Focusing on those who wore the most visually distinct clothes--priests, women religious, and schoolchildren--the story begins in the 1830s, when most American priests were foreign born and wore a variety of clerical styles. Dwyer-McNulty tracks and analyzes changes in Catholic clothing all the way through the twentieth century and into the present, which finds the new Pope Francis choosing to wear plain black shoes rather than ornate red ones.--Publisher description.